IMPLEMENTASI KEBIJAKAN PENGENDALIAN ALIH FUNGSI LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Irawan, Aca; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Conversion of agricultural land into Non Agricultural become a serious problem, which in essence is of particular concern, it is happening in District transverse Rimba Rokan Hilir, the tendency of the transfer function in this agricultural land into oil palm plantations is, along with the rate of rice farmland alihfungsi happened which has increased from year to year, from the year 2011-2012 were 1120.2 hectares of rice farmland converted to oil palm plantations in the District Jungle Crossing. With the issuance of Law No. 41 of 2009 on the Protection of Agricultural Land Sustainable Food, the aim of this study examines the implementation and the factors that influence achievement and efforts of sustainable food agriculture protection and control over the function of sustainable agricultural land. So that no agricultural land in the District Jungle rice Across functioned over to oil palm plantations.The method used in this study is descriptive, descriptive research method is done by analyzing the data and data collection fakta.Teknik using interview techniques, observation and documentation. The results show the implementation of Law No. 41 Year 2009 in Rokan Hilir districts particularly in the Jungle Crossing is still at the stage of identification lokasi.Hasil location identification has been carried out by the Department of Agriculture in 2012 showed that the sustainable protection of agricultural land need to be implemented to control over land use, food security and environmental sustainability. In the implementation, there should be a clear and unequivocal rule set on protected farmland, sanctions in the event of conversion of the protected land, and incentives which will be accepted by society if protecting agricultural land.Keywords: Policy, Land Transfer Functions, Protection